1998
DOI: 10.1046/j.1365-2567.1998.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal natural killer cell function is suppressed

Abstract: Previous studies have reported reduced natural killer (NK) cell activity in cord blood (CB) compared with adult blood mononuclear cell populations. Using a non-radioactive killing assay, we have verified these findings suggesting that either the fetal NK cell function is suppressed or that these cells are functionally immature. We have shown that CB NK cells are functional, since activating them with cytokines known to activate adult NK cells [interleukin-2 (IL-2), IL-12 and IL-15] increased activation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Berg et al showed that cryopreservation of expanded NK cells reduced expression of NKG2D and TRAIL and NK cell cytotoxicity, although this effect could be reversed by exposure of NK cells to IL-2 [37]. However, Dominguez et al observed that CB MNCs had their NK activity were restored by freeze/thawing, suggesting that the cytotoxic capacity of fetal NK cells was suppressed in vitro [38]. The effect of cryopreservation on NK function of purified UCB NK cells compared to their adult counterparts awaits further study.…”
Section: Cytotoxic Function Of Ucb Nk Cellsmentioning
confidence: 99%
“…Berg et al showed that cryopreservation of expanded NK cells reduced expression of NKG2D and TRAIL and NK cell cytotoxicity, although this effect could be reversed by exposure of NK cells to IL-2 [37]. However, Dominguez et al observed that CB MNCs had their NK activity were restored by freeze/thawing, suggesting that the cytotoxic capacity of fetal NK cells was suppressed in vitro [38]. The effect of cryopreservation on NK function of purified UCB NK cells compared to their adult counterparts awaits further study.…”
Section: Cytotoxic Function Of Ucb Nk Cellsmentioning
confidence: 99%
“…Deficient immune function in neonates is characterised by relatively deficient functioning of innate and antigenspecific immunity [49,56]. Defective functions of the cells of the innate immune system consist of delayed recruitment of neutrophils and monocytes to infected tissue and diminished natural killer cell cytotoxicity [57]. During the neonatal period antigen presentation by macrophages and dendritic cells is less efficient, possibly due to deficient IL-12 production, resulting in slow development of antigen-specific immunity [48,49,58].…”
Section: Immature Immunity As a Cause Of Severe Rsv Bronchiolitismentioning
confidence: 99%
“…This dysfunction or immaturity of neonatal NK cells may reduce the capacity of neonates to respond to viral infections (20,(23)(24)(25). The decreased function of cord blood and neonatal NK cells may be partly due to an undefined suppressive mechanism (19). A more recent study suggests that CD4 ϩ CD25 ϩ T regulatory cells could decrease NK cell production of IFN-␥ and perforin, most likely through a direct cell-to-cell interaction (26).…”
mentioning
confidence: 99%
“…A more recent study suggests that CD4 ϩ CD25 ϩ T regulatory cells could decrease NK cell production of IFN-␥ and perforin, most likely through a direct cell-to-cell interaction (26). The phenotype of NK cells derived from cord blood is different from that seen in adults, most notably in the lack of CD57 expression found on many adult CD56 dim NK cells (19,27,28). Adult CD57 ϩ NK cells are thought to represent senescent cells that have proliferated in vivo (20,29,30).…”
mentioning
confidence: 99%